Insulin sensitivity in moderately severe to acute severe ulcerative colitis - Daniel Bergemalm; Bayar Baban; Olle Ljungqvist; Jonas Halfvarson (2025)
Background Patients hospitalized with moderately severe or acute severe ulcerative colitis (UC) may experience metabolic disturbances, including alterations in insulin resistance due to inflammation and the administration of glucocorticoids (GCs). This pilot study aimed to evaluate insulin sensitivity in patients hospitalized for moderately severe to severe UC.